IDENTIFICATION OF LOCAL WISDOM VALUES THAT GROW AND DEVELOP IN COMMUNITIES IN CREATIVE TOURISM AREAS AROUND SAMOSIR, INDONESIA - D. Sitohang, Ance Marintan (JURNAL PENDIDIKAN ILMU SOSIAL, 2020)
The purpose of this study is to identify the types and values contained in the types of local wisdom that grow and develop in communities in the Creative Tourism Area, Simanindo District, Samosir Regency, North Sumatra. The sample in this study amounted to 30 people who were selected non-probability using the snowball technique. The data were obtained using a survey method using a questionnaire which was analyzed using qualitative methods. The results showed that in Simanindo Subdistrict, there can still be found a number of cultural values of local wisdom (both in physical and non-physical form) in the lives of the people who live in this area. Even so, not a few have experienced value shifts and extinction. In general, local wisdom can be classified into five values, namely cultural, social, religious, molar, and economic.